2021
DOI: 10.1093/eurpub/ckab190
|View full text |Cite
|
Sign up to set email alerts
|

PM10 exposure interacts with abdominal obesity to increase blood triglycerides: a cross-sectional linkage study

Abstract: Background Blood lipids and glucose levels dysregulation represent potential mechanisms intermediating the adverse cardiovascular effects of ambient particulate matter (PM) exposure. This study aims to estimate the effect of long-term PM10 exposure on blood lipids and glucose levels and to assess the potential mediation and/or modification action of abdominal obesity (AO) (waist-to-height ratio). Methods Our study was based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Long term exposure to PM 10 was associated to lung cancer development risks modified antiviral factors production of peripheral blood mononuclear cells, and increased viral replication of SARS-CoV-2 [11,12]. Exposure to PM 10 increased blood triglycerides even at low levels [13]. Anti-inflammatory compound biochanin A could alleviate PM 10 -induced acute pulmonary cell injury in vitro [14].…”
Section: Pm 10mentioning
confidence: 98%
“…Long term exposure to PM 10 was associated to lung cancer development risks modified antiviral factors production of peripheral blood mononuclear cells, and increased viral replication of SARS-CoV-2 [11,12]. Exposure to PM 10 increased blood triglycerides even at low levels [13]. Anti-inflammatory compound biochanin A could alleviate PM 10 -induced acute pulmonary cell injury in vitro [14].…”
Section: Pm 10mentioning
confidence: 98%
“…TC was positively correlated with long-term exposure to particles with diameters ≤1.0 µm (PM 1 ), particles with diameters ≤2.5 µm (PM 2.5 ), PM 10 , and carbon monoxide (CO); TG was positively correlated with long-term exposure to PM 10 ; HDL-C was negatively correlated with long-term exposure to PM 1 , PM 10 , sulfur dioxide (SO 2 ), and CO; and LDL-C was positively correlated with long-term exposure to PM 2.5 and PM 10 . Because air pollution persists and its harm to people is longterm, most studies are aimed at long-term air pollution exposure [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. A few studies have shown that short-term air pollution levels can also bring about changes in blood lipids [28][29][30][31][32][33][34][35].…”
Section: Association Between Air Pollution and Blood Lipidsmentioning
confidence: 99%
“…Many studies have reported that air pollutants are significantly associated with the increase in TG, TC, and LDL-C or the decrease in HDL-C. However, most studies reported that air pollution was associated with adverse changes in 1-3 lipid indexes, and the changes in the others are beneficial or not significant [6,10,[12][13][14][15][16][17][18]20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35]38,48]. A few studies reported that air pollution was associated with adverse changes in all four conventional lipid indexes [19,21,56], such as the study of Wang et al, which showed that a 10 µg/m 3 increase in PM 2.5 concentration was associated with a 0.92% increase in TC, a 2.23% increase in TG, a 3.04% increase in LDL-C, and a 2.03% decrease in HDL-C [19].…”
Section: Indicators Of Lipid Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies sµggested PM acts as an environmental endocrine disruptor for blood glucose, including insulin resistance and lipid hemostasis, by increased adipokine secretion [14]. In their analysis, Marin-Palma et al [15] noticed the increased production of pro-inflammatory cytokines, such as IL-1β and IL-6, with PM10 exposure.…”
Section: Introductionmentioning
confidence: 98%